Von Mises, Kantorovich and in-natura calculation - W. Paul Cockshott (Intervention. European Journal of Economics and Economic Policies, 2010)
The article reviews the idea of calculation in kind. It is argued that Kantorovich and subsequent mathematicians essentially validated the idea of in-kind calculation. This has not been evident because Kantorovich nowhere deals with the Austrian school and they for their part have ignored him. The article continues by examining improvements in linear optimisation since Kantorovich and the implications these have for economic planning. Finally it discusses the problem of deriving the plan ray in the context of markets for consumer goods.
Keywords: C61; B14; 330; planning; calculation debate; linear optimisation